The role of the collective making of identity in health promotion in the Hlokomela project, Hoedspruit, Limpopo, South Africa - Cockayne, Patrick William (My University, 2016)
Introduction: Migrant farm workers in South Africa are particularly vulnerable to HIV infection for a multitude of reasons, including a lack of access to health services and to health information. Social norms on the farms, including an acceptance of multiple concurrent sexual partners and transactional sex both for comfort and material gain, tend to worsen women's powerlessness to manage effectively their sexual reproductive health. High levels of stigma also mean that the risks of HIV infection cannot easily be spoken about, further increasing vulnerability. The Hlokomela project sought to use participatory communication processes to empower peer communicators on the farms to engage farm workers in regular, structured discussions on HIV /AIDS and other health and wellness related matters, including difficult conversations around gender inequity. The making of a collective identity for the project was one of these participatory processes. Its novelty in this setting warranted research to answer the question "How does (or does) the collective making of a project identity help to promote health on the farms of Hoedspruit?". Aim: The aim of the research was to describe and analyse the role of collective identitymaking in the Hlokomela project, an intervention to address vulnerability to HIV among migrant and seasonal farm workers in Hoedspruit, Limpopo province, South Africa. The study aimed also to propose and further develop, in the light of Findings, a conceptual framework which would help to explain the effects of the various elements of collective identity-making. Methods: The research is a qualitative study of the collective identity-making component of the Hlokomela health project. Elements of a grounded theory approach were adopted in the three successive data collection site visits, enabling progressive coding of the data as the collection occurred. Data was collected through two Focus Group Discussions (FGD) with Nompilos (farm worker volunteer peer communicators and care givers) and two FGDs with Gingirikani (farm worker volunteer peer communicators chosen by Nompilos and farm workers to be their deputies on the farms, to facilitate purposive dialogues and thus increase reach). There were also 10 individual in-depth interviews with other key stakeholders and three small group interviews (2-3 respondents) with Hlokomela managers and co-ordinators. All interviews were audio-taped, transcribed and where necessary translated into English from Xitsonga and Sepedi. The voices of those most directly affected by the intervention formed the basis for coding and analysis. Findings: The development of the collective identity through participatory processes was found to enhance engagement with and among farm workers. This was due to the project's perceived pertinence and local ownership. The collective identity was seen to be relevant and expressing a farm worker reality. Farm workers generally described feeling affirmed, seeing themselves projected into a public space that had hitherto not been open to them. And also in particular, the agents of the project – the Nompilos and their "deputies" the Gingirikani – described at length how being associated with Hlokomela gave them the authority and credentials to work with farm workers on sensitive matters, including establishing a set of values and norms which would be health-protective but which also involved a shift in what was considered possible and desirable. There was furthermore a sense of belonging to the project, not only on the part of the primary "beneficiaries" – farm workers – but also of other stakeholders, including farm owners/managers, municipal office bearers, and local health workers. This bridging social capital further augmented the project's capacity to reach farm workers by, for example, enabling access in working time on the farms, by donations in money and in kind by the local community, and by making visible and normal what hitherto had been hidden – particularly in terms of gender equity and a softening of hegemonic masculinities. Farm workers could take the lead, and women could take the lead also. Conclusions: The collective identity-making work of Hlokomela had aided the project's agents to nurture a new possible, founded in a slightly altered set of values and norms, which had the potential to reduce vulnerability to HIV infection. The elaboration of a social institution, largely in the symbolic space, had authorised the project's agents, in their own eyes as well as those of their peers, to carry out their often difficult work of facilitating regular dialogues on hitherto rarely broached topics, including gender relations and risky sexual behaviour. The findings indicate a need for further research into the cost effectiveness and replicability of this kind of identity work in similar projects, perhaps with the addition of quantitative assessments of the extent of projects' reach through collective identity work as well as the value of collateral beneficial effects to participants in resource poor settings.
A dissertation submitted to the School of Public Health, University of the Witwatersrand, in fulfillment of the requirements for the degree of Master of Science in Medicine by research and dissertation. 07 June 2016
Keywords: Health Promotion; Farmers; Transients and Migrants; HIV